2015
DOI: 10.1371/journal.pone.0142077
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Toll-Like Receptor 4 Function Partially Protects against Peripheral and Cardiac Glucose Metabolic Derangements During a Long-Term High-Fat Diet

Abstract: Diabetes is a chronic inflammatory disease that carries a high risk of cardiovascular disease. However, the pathophysiological link between these disorders is not well known. We hypothesize that TLR4 signaling mediates high fat diet (HFD)-induced peripheral and cardiac glucose metabolic derangements. Mice with a loss-of-function mutation in TLR4 (C3H/HeJ) and age-matched control (C57BL/6) mice were fed either a high-fat diet or normal diet for 16 weeks. Glucose tolerance and plasma insulin were measured. Prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Pyruvate can then either enter the tricarboxylic acid (TCA) cycle in the mitochondria, where it undergoes oxidative phosphorylation in a process that requires oxygen, or it can be further converted into lactate (anaerobic glycolysis) (34). Mice with a loss-of-function mutation in TLR4 (C3H/HeJ) were partially protected against cardiac glucose metabolism dysregulation induced by a long-term high-fat diet (20). TLR4 regulates lipid accumulation in cardiac muscle in type 1 diabetes, which contributes to cardiac dysfunction (7).…”
Section: Discussionmentioning
confidence: 99%
“…Pyruvate can then either enter the tricarboxylic acid (TCA) cycle in the mitochondria, where it undergoes oxidative phosphorylation in a process that requires oxygen, or it can be further converted into lactate (anaerobic glycolysis) (34). Mice with a loss-of-function mutation in TLR4 (C3H/HeJ) were partially protected against cardiac glucose metabolism dysregulation induced by a long-term high-fat diet (20). TLR4 regulates lipid accumulation in cardiac muscle in type 1 diabetes, which contributes to cardiac dysfunction (7).…”
Section: Discussionmentioning
confidence: 99%
“…GLUT4 is the key player in insulin-mediated glucose transport and its protein content is decreased in insulin-sensitive tissues of patients with diabetes. 38,58 -60 Accordingly, in the current study, STZ-treated rodents had significantly less GLUT4 protein content in a crude membrane extract of striated muscle than their control counterparts. Not only was this decrease not rescued by treatment with diltiazem, but it was further worsened in both cardiac and skeletal muscle.…”
Section: Discussionmentioning
confidence: 45%
“…Several studies further confirmed the protective metabolic effects of TLR4 deficiency [63][64][65][66] , as reviewed in 67 . Finally, the relevance of TLR4 was suggested in humans, as TLR4 expression, protein content and signaling is higher in muscle tissue of individuals with obesity and T2D than in lean controls 68 .…”
Section: Lps Effects On Insulin-resistance In Mice and Humansmentioning
confidence: 77%